303 nm continuous wave ultraviolet laser generated by intracavity frequency-doubling of diode-pumped Pr3+:LiYF4 laser. (1st March 2018) - Zhu, Pengfei; Zhang, Chaomin; Zhu, Kun; Ping, Yunxia; Song, Pei; Sun, Xiaohui; Wang, Fuxin; Yao, Yi
Highlights: High efficiency: With incident power of 10 W, 68 mW at 303 nm is achieved with high efficiency. Special CLBO: CLBO with the Brewster angle can reduce the loss of the UV laser without UV film. Cavity design: The V-shaped cavity satisfy the mode matching condition. Abstract: We demonstrate an efficient and compact ultraviolet laser at 303 nm generated by intracavity frequency doubling of a continuous wave (CW) laser diode-pumped Pr 3+ :YLiF 4 laser at 607 nm. A cesium lithium borate (CLBO) crystal, cut for critical type I phase matching at room temperature, is used for second-harmonic generation (SHG) of the fundamental laser. By using an InGaN laser diode array emitting at 444.3 nm with a maximum incident power of 10 W, as high as 68 mW of CW output power at 303 nm is achieved. The output power stability in 4 h is better than 2.85%. To the best of our knowledge, this is high efficient UV laser generated by frequency doubling of an InGaN laser diode array pumped Pr 3+ :YLiF 4 laser.